Trinucleotide Repeat Protocols - Kohwi, Yoshinori; McMurray, Cynthia T.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Two decades have passed since trinucleotide repeat expansion was first discovered in genes responsible for certain neurological diseases. Since then, new technologies have developed and innovative concepts have emerged, which may prove useful in devising therapeutic approaches to neurological diseases. Divided into six convenient sections, Trinucleotide Repeat Protocols, Second Edition covers a wide range of topics such as an overview of trinucleotide repeat diseases, synaptic plasticity, embryonic stem (ES) cell-related protocols with a focus on HD, RNA-related protocols, and analysis of epigenetic modification in fragile X syndrome.  This edition focuses not only on direct analysis of trinucleotide repeat diseases but also on alternative approaches for the analysis of trinucleotide repeat diseases, with the hope that this will result in a better understanding of the mechanisms and future therapeutic prospects for treatment of these diseases. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Trinucleotide Repeat Protocols, Second Edition seeks to serve researchers with its thorough methodologies on this expanding field.
A Brief History of Triplet Repeat Disease -- Huntington's Disease and Cell Therapies: Past, Present and Future -- Transcranial Two-Photon Imaging of Synaptic Structures in the Cortex of Awake Head-Restrained Mice -- In vivo Imaging of Synapse Plasticity in the Mouse Motor Cortex -- Pluripotent Hybrid Stem Cells from Transgenic Huntington’s Disease Monkey -- Mesenchymal Stem Cells for Trinucleotide Repeat Disorders -- Lentiviral-Mediated Gene Transfer of siRNAs for the Treatment of Huntington's Disease -- Purification of dFMR1-Containing Complexes Using Tandem Affinity Purification -- Combined FISH and Immunofluorescent Staining Methods to Co-localize Proteins and mRNA in Neurons and Brain Tissue -- Epigenetic Modifications of the FMR1 Gene -- The CGG Repeat and the FMR1 Gene -- Study of Oxidative Damage and Antioxidant Systems in Two Huntington´s Disease Rodent Models -- Regulation of Ataxin-1 Phosphorylation and Its Impact on Biology -- Towards Understanding Region-Specificity of Triplet Repeat Diseases: Coupled Immunohistology and Mass Spectrometry Imaging -- Antibodies and Intrabodies Against Huntingtin: Production and Screening of Monoclonals and Single-Chain Recombinant Forms -- Cell Recovery from DM1 Transgenic Mouse Tissue to Study (CTG)n Instability and DM1 Pathogenesis -- Markerless Modification of Trinucleotide Repeat Loci in BACs -- DRPLA: Recent Advances in Research Using Transgenic Mouse Models.
Keywords: Molecular biology; Gene expression; Molecular Medicine; Gene Expression